The drivers of student enrolment and retention: a stakeholder perception analysis in higher education - Angelopulo, George (Faculty of Law, University of the Free State, 2013)
This study identified the drivers of student participation in the academic programmes of a South African university department. First, it explored the determinants of student enrolment and retention from earlier research and literature. Second, it discussed the utility of Q methodology in the identification of subjective perception. Finally, it isolated dominant perceptions of the factors that govern enrolment and retention in the academic programmes of the Department of Communication Science at the University of South Africa. The research was undertaken amongst a diverse group of students, faculty, support and oversight staff, chosen to represent as wide a range of opinions on the topic as possible. Q methodology was used to categorise the variety and span of subjective opinion on the market-related, service quality and cultural variables that support or undermine student participation in the department’s academic programmes. Eight richly diverse accounts were derived, reflecting the most salient perceptions on the topic. Underlying factors that supported student enrolment and retention were the reputation, credibility and image of university and department, and specific academic, disciplinary, technical and administrative competencies. The main factors that undermined enrolment and retention were the scope of research and tuition, institutional performance, inconsistency in teaching quality and the relative inaccessibility of tuition material. The research framework described in this paper offers a promising resource for the student development strategies of academic institutions.
Keywords: Student enrolment; Student retention; Higher education; Q methodology; Student development strategy; Unisa; Communication; Solution meaning; Perception analysis; Brand perception; University marketing